Language of sport vs. the expression of emotions − a new (?) research perspective - Grochala, Beata (Papers in Linguistics, 2019)
Emotions in the language of sport have been studied primarily from the perspective of the language of commentators, especially television. This article presents a different approach to emotions in the language of sport. On the one hand, the analysis of the language of on-line relations and, on the other hand, the language of supporters were analysed. The latter is considered ugly, vulgar and full of offensive terms. On the basis of the inscriptions on the walls and songs of sports fans, an attempt was made to prove that this is not always the case. This article is an attempt to show a new direction in the study of emotions in the language of sport, i.e. taking into account the perspective of a general recipient (not just the media recipient).